Dampak Tayangan Log In terhadap Implementasi Prinsip-Prinsip Komunikasi Islam dalam Masyarakat - Syifa Hayatin Nufus (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
Technological developments require da’wah to update its concept to be more modern and not left behind. So Log In is present as a da’wah media that follows the development of the times, both in terms of technology and social aspects. Log In content is an effective da’wah media for the current generation, by following social life updates that are running quite quickly. The communication method in the “Log In” podcast has applied the principles that exist in Islamic communication. With the “Log In podcast, a significant influence on society began to be seen. Millions of loyal viewers of this podcast began to be influenced by the contents of the da’wah message conveyed, and some of them even began to practice it in their daily lives. This shows that the principles of Islamic communication, such as honesty, patience, politeness, and empathy, can be applied effectively in various contexts, providing a broad positive impact on listeners and society in general